Reminiscing the significance on historical site of Fort Margherita through urban riverfront design along Sg. Sarawak. (Pangkalan Sapi To Kpg Boyan) Kuching, Sarawak - Bujang, Nashahirah (2018)
Historical place and cultural heritage plays huge role in development of internal tourism. The main point of historical and cultural heritage is become important and as a asset of the cities. It is a real opportunities of economic, social and cultural. The history can be polish with the place that was originally historic but in adaptation to be a successful riverfront development. By enhancing the local physical character, it will emphasized on the function of open spaces, waterfront connectivity and conservation of historical feature. Also, the significance of this study also to emphasized on promoting the cultural tradition of Sarawak which is create a sense of place and living culture center at the historical place. The methodology of this study involves implementation stages of existing data from previous researchers which been published and support with secondary data from government department. Identification for primary data through observation and data recorded method. The data collected from the inventory are synthesized to identify the potential area to be enhancing the value of historical of the Dynasty Brooke to Sarawak. This study is hoped to provide a functional and a guide to landscape architecture urban studies in creating a sense of place and historic value which involved a space towards enhancing and promoting the historical value in Sarawak.